Not that kind of girl a young woman tells you what she's "learned" - Dunham, Lena 1986- (Random House, 2015)
""If I could take what I've learned and make one menial job easier for you, or prevent you from having the kind of sex where you feel you must keep your sneakers on in case you want to run away during the act, then every misstep of mine was worthwhile. I'm already predicting my future shame at thinking I had anything to offer you, but also my future glory in having stopped you from trying an expensive juice cleanse or thinking that it was your fault when the person you are dating suddenly backs away, intimidated by the clarity of your personal mission here on earth. No, I am not a sexpert, a psychologist or a dietician. I am not a mother of three or the owner of a successful hosiery franchise. But I am a girl with a keen interest in having it all, and what follows are hopeful dispatches from the frontlines of that struggle.""...
Keywords: Dunham, Lena -- 1986-; Television producers and directors -- United States -- Biography; Actors -- United States -- Biography